Discovery of a bone‐like blood particle in the peripheral circulation of humans and rodents. (21st July 2019) - Prisby, Rhonda; Ross, Jean; Opdenaker, Lynn; McLane, Mary Ann; Lee, Seungyong; Sun, Xiangle; Guderian, Sophie
Abstract: Objective: To characterize ossified bone marrow blood vessels and confirm the presence of ossified particles (OSP) in humans and rodents. Methods: Human bone marrow blood vessels were processed for scanning and transmission electron microscopy. Whole blood samples were collected from younger (26‐39 years; n = 6) and older (55‐63 years; n = 6) volunteers and male Fischer‐344 rats (1 month, n = 7; 6 months, n = 7; 12 months, n = 7; 18‐months, n = 6; 24 months, n = 8). OSP in the whole blood samples were sorted and imaged with microscopy to determine diameter, circularity, and solidity. Additionally, the chemical composition of OSP was determined via elemental analysis. Results: SEM revealed two types of ossified bone marrow blood vessels: that is, "transitioning" and "ossified." OSP were adhered to the surface of transitioning vessels and theoretically gain access to and circulate within the blood. The majority of OSP were ≤15 μm in diameter, but many were of sufficient size to serve as emboli (ie, >15 μm).OSP were predominately oblong in shape and several had jagged tips and edges. Conclusions: We introduce a novel, bone‐like blood particle that may be diagnostic of bone marrow blood vessel ossification. Further, OSP may associate with several disease states (eg, atherosclerosis).